2016
DOI: 10.1007/s00296-016-3473-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long- and short-term interdisciplinary treatment approaches in women with fibromyalgia: a randomized controlled trial

Abstract: We investigated the effects of long- and short-term interdisciplinary treatment approaches for reducing symptoms and improving health-related quality of life (HRQoL) and physical functions of patients with fibromyalgia and compared the effects of two different interdisciplinary treatment approaches. We conducted a prospective, randomized, controlled trial involving 66 women with fibromyalgia eligible for the study at a university hospital setting. The patients were randomized into three groups (allocation rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 55 publications
0
46
0
1
Order By: Relevance
“…21,26,30,[40][41][42][54][55][56] In addition to the above findings, there are studies mentioned in this review which showed low or no treatment effect or insignificant group differences in terms of primary and/or secondary variables. 24,42,43 One should not disregard that all these may actually be related with five major methodological problems which are differences in number of sessions, employment of varying assessment tools, lack of (active) control group or RCTs, the absence and features of follow-up evaluations, and drop-out rates. Firstly, in terms of number of sessions, even though more intense and more frequent long-term interventions are suggested to enhance the effectiveness of the interventions, 57 there is a gradual increase in the number of interventions employing brief CBT modules because of its cost-effectiveness.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…21,26,30,[40][41][42][54][55][56] In addition to the above findings, there are studies mentioned in this review which showed low or no treatment effect or insignificant group differences in terms of primary and/or secondary variables. 24,42,43 One should not disregard that all these may actually be related with five major methodological problems which are differences in number of sessions, employment of varying assessment tools, lack of (active) control group or RCTs, the absence and features of follow-up evaluations, and drop-out rates. Firstly, in terms of number of sessions, even though more intense and more frequent long-term interventions are suggested to enhance the effectiveness of the interventions, 57 there is a gradual increase in the number of interventions employing brief CBT modules because of its cost-effectiveness.…”
Section: Discussionmentioning
confidence: 59%
“…With respect to this two-fold classification in terms of outcomes and treatment modalities, this review overall delineates that CBT was the most frequently utilized psychotherapeutic modality of GP interventions, be it a MT or a U/GP. 21,24,25,29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] On the other hand, other few interventions including different psychotherapeutic approaches (which are mindbody intervention, mindfulness based therapy, short-term psychodynamic psychotherapy, acceptance commitment therapy) aside from CBT were also utilized. 23,[45][46][47][48] However, the results of the studies revealed some inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A seguir, encontra-se um quadro com detalhamento com informações de acordo com o autor, ano de publicação, país de origem, objetivo e o delineamento da pesquisa (Quadro 1). 15 dor, fadiga, qualidade do sono, sintomas (2016) depressivos, melhoria da QVRS e de funções físicas. Avaliar, quantitativa e qualitativamente, Ensaio clínico 6 Bourgault P, Lacasse A, a eficácia de uma intervenção randomizado Marchand S, et al 16 Canadá interdisciplinar para o autogerenciamento.…”
Section: Issn 2236-5834unclassified